Approximation of max independent set, min vertex cover and related problems by moderately exponential algorithms - Bourgeois, Nicolas; Escoffier, Bruno; Paschos, Vangelis Th (Discrete Applied Mathematics, 2011)
Using ideas and results from polynomial time approximation and exact computation we design approximation algorithms for several NP-hard combinatorial problems achieving ratios that cannot be achieved in polynomial time (unless a very unlikely complexity conjecture is confirmed) with worst-case complexity much lower (though super-polynomial) than that of an exact computation. We study in particular two paradigmatic problems, max independent set and min vertex cover. ► We propose exponential time approximation algorithms for solving NP-hard problems. ► This approach is considered for Max Independent Set and Min Vertex Cover. ► We achieve interesting tradeoffs between running times and approximation ratios. ► Used techniques are splitting of the instance, parameterized algorithms, randomization.